Representasi Pesan Edukasi dalam Film “Di Bawah Umur” (Analisis Semiotika John Fiske Tentang Perilaku Remaja Gen-Z) - Amelia, Desi; Sikumbang, Ahmad Tamrin (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research was carried out with the aim of further identifying the educational messages contained in the film Under Age by using 3 levels in John Fiske’s Semiotic analysis, namely the level of reality, representation and ideology. Researchers used qualitative research methods with a descriptive approach. The research results show that in this film there are many educational messageto be conveyet to the audience, such as conveying the values of frienship, family value, and honestywhich must be uphelp as highly as possible within every human being. The educational message from the level of reality that can be seen in that the environment influences the behavior of teenagers who are still searching for their identity. The level of representation depicted is a shooting technique that focuses on medium shots and close-up shot so that you can see the character’s expressions clearly, as well as the level of ideology in the film. Thus is the ideology of socialism with middle class social life.